2007
DOI: 10.1007/s11258-007-9325-6
|View full text |Cite
|
Sign up to set email alerts
|

How does light and phosphorus fertilisation affect the growth and ectomycorrhizal community of two contrasting dipterocarp species?

Abstract: Phosphorus concentrations in many south-east Asian tropical rain forest soils are very low. To determine the growth responses of seedlings of a light-demanding (Shorea leprosula) and a more shade-tolerant (Hopea nervosa) dipterocarp species to increasing P, we carried out a nursery fertilisation experiment. Responses of symbiotic ectomycorrhizal (EcM) fungi to the treatments were also determined. Seedlings were grown under high light (13 mol m À2 d À1 ) or moderate light (4 mol m À2 d À1 ) in shade-chambers an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
1
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 44 publications
0
26
1
2
Order By: Relevance
“…The limited response of survival and growth to inoculation and the abundance of EcM of different morphotypes in all locations where S. lamellata and S. selanica were outplanted was unexpected and different from what has been reported for early growth of dipterocarp species from Borneo (Smits 1994;Turjaman et al 2007;Brearley et al 2007). Our results challenge, at least for lowland Sumatra, the concept that lack of EcM is a primary constraint on the use of dipterocarps for enrichment planting.…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…The limited response of survival and growth to inoculation and the abundance of EcM of different morphotypes in all locations where S. lamellata and S. selanica were outplanted was unexpected and different from what has been reported for early growth of dipterocarp species from Borneo (Smits 1994;Turjaman et al 2007;Brearley et al 2007). Our results challenge, at least for lowland Sumatra, the concept that lack of EcM is a primary constraint on the use of dipterocarps for enrichment planting.…”
Section: Discussioncontrasting
confidence: 80%
“…Seedlings of both species grew better in the open areas, such as ExForest_1 and ExRAF_1. Previous studies have shown growth of dipterocarp seedlings (mainly Shorea) to be enhanced in well illuminated conditions (Tennakoon et al 2005;Brearley et al 2007) and to show a positive correlation with gap distance (Otsamo 2000).…”
Section: Land History and Light Condition Effectsmentioning
confidence: 98%
“…In Borneo, many soils are N-and P-limited (Nomura and Kikuzawa 2003;Paoli et al 2005;Paoli 2006); e.g., typically, soil (NH 4 OAc/HOAc)-extractable concentrations are <1 Pg P g -1 (Brearley et al 2007). In nutrient-limited tropical ecosystems, plant defences against leaf herbivores can be adaptations to avoid the loss of nutrients.…”
Section: Introductionmentioning
confidence: 99%
“…In non-ericaceous plants, shading usually reduces the levels of carbon-based secondary chemicals (Hartley et al 1997;Henriksson et al 2003, Ruohomäki et al 1996Iason et al 1996). In plants with ectomycorrhizal fungal symbionts, shade effects on the amount of colonisation or amounts of structures are ranging from no effect (Brearly et al 2007;Dehlin et al 2004) to decreased colonisation rates (Becker 1983;Ingleby et al 1998) or even increased colonisation rates (Prajadinata and Santoso 1993;Be'reau et al 2000). As these ectomycorrhizal fungi produce a Hartig net around the roots, we assume that they show a different response to shading compared to ericoid mycorrhizal fungi, which only proliferate within the epidermal cells of roots.…”
Section: Introductionmentioning
confidence: 99%